Comparison of maternal and neonatal outcome of IVF/ICSI conceived pregnancies with spontaneous conceived pregnancies - Patil, Preeti; Karthik, Gayathri (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Conception by IVF has been associated with an increased incidence of several obstetrical and perinatal complications. IVF is associated with increased complications like OHSS (Ovarian Hyper Stimulation Syndrome), multiple pregnancies and thromboembolism, ectopic pregnancy, congenital malformations, and small for gestational age, low birth weight etc. This study is done to evaluate and compare the obstetric and perinatal complications between assisted reproduction and spontaneous conception. The objective of the present study was to evaluate and compare the maternal and neonatal outcome of IVF/ICSI conceived pregnancies with spontaneous conceived pregnancies. Methods: In this study 62 patients conceived with IVF/ICSI were taken as cases and 62 patients conceived spontaneously were taken as controls. The categorical data was analyzed using chi square test and results expressed by p value. Results: The incidence of multiple pregnancies among IVF/ICSI group is 33.8% and 1.6% in controls. IVF/ICSI conception when compared to spontaneous conception is associated with increased incidence of miscarriage (18% versus 1.6%), first trimester bleeding (18% versus 1.6%), cervical insufficiency (22.5% versus 0), PROM (11.3% versus 1.6%), preterm birth (33.8% verss 14.5%), caesarean section rates (71% vs 53%), low birth weight babies (44% vs 10.7%) and NICU admissions(33.3% vs 10.7%). The male: female ratio is higher in IVF/ICSI group. Conclusions: IVF/ICSI conceptions are associated with a significantly higher incidence of multiple pregnancies, miscarriage, prematurity, increased caesarean section rates, and increased male: female ratio.